Potensi Pengembangan Industri Biomassa Wood Pellet di Indonesia dengan Analisis BCG dan SWOT - Santika Sari Sari; Claudia Sitorus (President University, 2021)
Energy needs in Indonesia tend to increase from year to year due to population growth and economic growth. This is a challenge for national energy security to be able to balance the amount of supply with the amount of demand (it is estimated that demand in 2035 will be three times higher than the current demand). Biomass is an environmentally friendly fuel that can be used as a substitute for fossil fuels to reduce global warming. Indonesia is believed to have the potential to become one of the main players in the world wood pellet industry. However, Indonesia's wood pellet production is still relatively small, which is around 80,000 tons per year. Therefore, it is important to dig deeper. To analyze the potentials associated with the Wood Pellet Biomass Industry in Indonesia, two methods can be used, namely BCG analysis and SWOT analysis. From the BCG analysis, it is found that Indonesia is in the Question Mark position for the wood pellet industry, with the value of market growth rate, and relative market share of 87.2270943% and 0.08756403 respectively. Thus, the most suitable SWOT strategy to be applied to the Question Mark position is the SO (Strength-Opportunity) strategy, namely; maximizing the natural resources owned, starting from the availability of land and the availability of existing plants to meet national energy and international markets, as well as supporting the Paris protocol policy